Calculation Mars – Earth distance and Mars orbital elements with Julian date - Qahtan, Atared Y. (Iraqi Journal of Physics, 2023)
In this paper, the Mars orbital elements were calculated. These orbital elements—the major axis, the inclination (i), the longitude of the ascending node (W), the argument of the perigee (w), and the eccentricity (e)—are essential to knowing the size and shape of Mars’ orbit. The quick basic program was used to calculate the orbital elements and distance of Mars from the Earth from 25/5/1950 over 10000 days. These were calculated using the empirical formula of Meeus, which depended on the Julian date, which slightly changed for 10000 days; Kepler’s equation was solved to find Mars’ position and its distance from the Sun. The ecliptic and equatorial coordinates of Mars were calculated. The distance between Mars and the center of the Earth, in astronomical units (A.U.), was calculated. RM-E(min) was found to be between 0.4763 and 0.5108, and RM-E(max) was found to be between 2.548 and 2.6259. Furthermore, the findings revealed that the Mars orbital elements have changed over time.